IMPLEMENTATION OF ZONING SYSTEM POLICY ON NEW STUDENTS’ ADMISSION OF HIGH SCHOOL LEVEL IN BOJONEGORO REGENCY - Rupiarsieh Rupiarsieh; Musta’ana Musta’ana (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
The zoning system of Admission of New Students (PPDB) 2018 has been highlighted. This system is considered to be detrimental to pupils, especially successful students. Since the zoning system was introduced, there have been many complaints and grievances from some students' parents, because the zone system prioritizes the closest home distance to the school of destination and ignores the national test results. This study aims to determine the implementation of the Zoning System Application Policy for the Admission of New Students in the 4th Bojonegoro State High School in the 2021/2022 academic year. The results show that the socialization of the zoning system policy in the admission of new pupils is carried out by the school to the target group through social media. However, there are still parents who are unaware of the policy due to a lack of reading the news on social media. In terms of human resources, it is sufficient to support all activities in the implementation of the policy. The implementer's position in the implementation of the zoning system policy is very well visible in the commitment and attitude of the implementers towards a program or policy. The bureaucratic structure of 4 Bojonegoro State High School in the implementation of the zoning system of admission of new pupils has been quite well seen from the division of work in PPDB where it divides two special teams namely teams for implementation PPDB and special teams for complaints.